Reaping the Whirlwind : The Taliban Movement in Afghanistan - Griffin, Michael, 1951- (Rawalpindi, Pakistan Army Education Publishing House, 2003)
Reaping the Whirlwind provides the first comprehensive profile of the Taliban in the twenty-first century. Drawing on numerous interviews with key protagonists, conducted over a period of several years, Michael Griffin provides a fascinating eyewitness account of the Afghan conflict. He explains the origins and beliefs of the Taliban movement, its religious and political ethos, and the character of its particular brand of so-called Islamic fundamentalism. Crucially, he examines the controversial nature of the Taliban's international links with the U.S., Saudi Arabia, and other vested interests. Griffin also explores the Taliban's connections with Osama bin Laden, drug barons and drug dealers, and the CIA's ambiguous relationship with what is often viewed as an international Islamist conspiracy." "Situated between Asia, the Middle East and the former Soviet states, Afghanistan has historically fulfilled the role of an artifical 'buffer state'.
Include Notes and Index
Keywords: Afghanistan -- Islamic fundamentalism -- Islam and politics -- Islam and state -- Taliban